Use the mathematical induction to show the given expression,
Step 1:
Consider I is the identity matrix of the order 2×2 ,
I=[ 1 0 0 1 ]
Let,
P( n ): ( aI + bA ) n = a n I + na n−1 bA, n∈N
Step 2:
For n=1 , the value of the left hand side (L.H.S.) is,
LHS= ( aI + bA ) 1 =aI + bA
And the value of the right hand side (R.H.S.) is,
RHS= a 1 I + 1a 1−1 bA = aI + a 0 bA =aI+bA
Here,
LHS=RHS
Hence, P( n ) is true for n=1 .
Step 3:
Consider the value of P( k ) is true so that,
P( k ): ( aI+bA ) k = a k I + ka k−1 bA, k∈N (1)
Step 4:
Proving that P(k + 1) is true.
Replace k with ( k+1 ) in the equation (1),
( aI + bA ) k+1 = a k+1 I+( k+1 ) a ( k+1 )−1 bA, k+1∈N ( aI + bA ) k+1 ︸ LHS = a k+1 I+( k+1 ) a k bA ︸ RHS
Consider left hand side of the above expression,
( aI + bA ) k+1 = ( aI + bA ) k ( aI + bA ) 1 = ( aI + bA ) k ( aI + bA )
From equation (1),
( aI + bA ) k+1 =( a k I + ka k−1 bA )( aI + bA ) =( aI + bA )( a k I + ka k−1 bA ) =aI( a k I + ka k−1 bA )+bA( a k I + ka k−1 bA ) =aI( a k I )+aI( ka k−1 bA )+bA( a k I )+bA( ka k−1 bA )
Further, simplify the above expression
( aI + bA ) k+1 = a k+1 I+ ka k−1+1 bA+ ba k A+( b 2 ) ka k−1 ( A 2 ) ( IA=A ) = a k+1 I+ ka k bA+ ba k A+ b 2 a k-1 ( A 2 ) (2)
Here, the value of the matrix A is given as,
A 2 =[ 0 1 0 0 ][ 0 1 0 0 ] =[ 0 0 0 0 ] =O
Substitute the value of A 2 in the equation (2),
a k+1 I+ ka k bA+ ba k A+ b 2 a k-1 ( O )= a k+1 I+ ka k bA+ ba k A = a k+1 I+ ba k A( k+1 ) =RHS
Hence, P( k+1 ) is true.
Therefore, by the mathematical induction this will prove that P( n ) is true for all n∈N .